Academic librarians' perception of non-formal continuing professional education programs in three university libraries in Metro Manila - Mendoza, Louise Kaye G.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
According to the BFL Code of Ethics, each and every librarian should strive to improve, enhance and upgrade their professional knowledge and skills through formal and informal means. Librarians should also live by the motto "C A N I - Constant and Never-ending Improvement". Although several studies have been done on the training needs of librarians, namely academic librarians, no studies have done so far on the assessment of CPE programs. This study aims to document, analyze and evaluate the continuing professional education (CPE) programs that are being sponsored by selected university libraries in Metro Manila for their employees.
This study conducted an interview of each of the head librarians of Ateneo de Manila University Rizal Library, University of Sto. Tomas Miguel de Benavides Library and University of the Philippines Diliman Main Library to determine the current CPE policies and programs being implemented and conducted by their corresponding library administrations. This study also used a survey questionnaire to establish the librarians' perception on the current non-formal CPE programs conducted by their respective library administrations.
Results showed that each university library has a set of policies that they follow in conducting and implementing CPE programs. Each of these libraries conducts seminars, conferences and workshops regularly and selects the topics according to the library's needs and innovations in the LIS profession.
The data revealed that all of the librarians from UP Diliman Main Library, UST Miguel de Benavides Library and ADMU Rizal Library find the non-formal CPE programs effective and helpful to their work. The respondents prefer to participate in seminars, conferences and workshops and these types of programs are the most effective for them. Despite the current knowledge and expertise that the librarians possess from formal and non-formal education, they still need further training on several aspects of library work. The availability of softwares on cataloguing, indexing and other electronic resources, however, does not take away the respondents' interests in further training on traditional aspects of library work such as cataloging and classification, research and indexing and abstracting.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Ateneo de Manila University Rizal Library; University of Santo Tomas Miguel de Benavides Library; University of the Philippines Diliman Main Library; Academic librarians -- Philippines -- Manila Metropolitan Area; Library education (Continuing education) -- Philippines -- Manila Metropolitan Area